Dynamics of retirements and pensioner profile in the central government - Sen, Pronab; Swain, Sibani (2007)
The prevailing state of information and analysis on issues trends in government employment, retirements, and future pension liabilities is highly unsatisfactory, and important decision are being taken on the basis of assumptions, which may not be founded on reality or even on rigorous theory. The costs of such ill-informed decisions can be substantial. The paper provides an appropriate methodology for projecting the future behaviour of government employment and pension liabilities so that there is some basis on which informed decisions can be taken regarding manpower planning in government. It finds that many of the commonly held beliefs are not rooted in reality. In particular, the view that the government can be downsized relatively painlessly is erroneous. This may not be a matter of much import, since the data suggests that the fiscal strain arising out of the salary bill of the Central government is not large enough to cause concern. The problems are elsewhere. Nevertheless, there may yet e a case for downsizing on the grounds of efficiency. In such a situation, careful consideration needs to be given to the method by which such a reduction is accomplished. - Reproduced.
Keywords: Civil service - India; Retirement - India; Pensions - India; Pensions